2008
DOI: 10.1016/j.cca.2008.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Detection of lung cancer using weighted digital analysis of breath biomarkers

Abstract: Background-A combination of biomarkers in a multivariate model may predict disease with greater accuracy than a single biomarker employed alone. We developed a non-linear method of multivariate analysis, weighted digital analysis (WDA), and evaluated its ability to predict lung cancer employing volatile biomarkers in the breath.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
171
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 210 publications
(176 citation statements)
references
References 28 publications
3
171
0
2
Order By: Relevance
“…This is the second published report of the use of electronic nose breath profiling in MM and substantiates the promise of this technique as a simple, easy way for detecting malignancy which has previously been reported for lung cancer [15,[17][18][19]. A study by DRAGONIERI et al [28] published very recently, while our paper was under review, also reports high levels of discrimination between patients with MM and those with long-term asbestos exposure using an electronic nose system, with results almost identical to those of our study.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This is the second published report of the use of electronic nose breath profiling in MM and substantiates the promise of this technique as a simple, easy way for detecting malignancy which has previously been reported for lung cancer [15,[17][18][19]. A study by DRAGONIERI et al [28] published very recently, while our paper was under review, also reports high levels of discrimination between patients with MM and those with long-term asbestos exposure using an electronic nose system, with results almost identical to those of our study.…”
Section: Discussionmentioning
confidence: 70%
“…Breath volatile organic compound (VOC) profiling can distinguish lung cancer patients from healthy controls with a high degree of sensitivity and specificity [5]. More than 4,000 VOCs have been found in exhaled breath, generated mainly from endogenous biochemical pathways including those of lipid peroxidation [15][16][17][18][19][20][21]. Techniques used for VOC analysis range from gas chromatography-mass spectrometry and ion mobility spectroscopy to colorimetric and gas sensors.…”
mentioning
confidence: 99%
“…Over the last few years, urine and breath analysis for the routine monitoring of metabolic disorders has attracted a considerable amount of scientific interest, due to painless, non-invasive sampling, and can be performed as often as needed [11]. Thousands of VOMs in trace amounts are present in human breath [12][13][14][15][16] and different studies have shown that the VOMs profile in patients with lung cancer can be discriminated from those of healthy subjects [12,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…styrene), siloxanes, methoxy-phenyl oxime (a solid phase microextraction [SPME] fiber-derived compound), etc. [8][9][10][11][12][13][14][15][16][17][18] We have been involved in studies where a large number of gas sampling bags are used for sampling exhaled breath. Since flushing Tedlar bags with pure nitrogen or air is not feasible due to many bags employed, we have looked for an alternative material for sampling bags.…”
Section: Introductionmentioning
confidence: 99%